P-OGC15 Impact of postoperative systemic treatment on survival for oesophageal adenocarcinoma after preoperative chemotherapy and oesophagectomy. (16th December 2021) - Rahman, Saqib; Thomas, Betsan; Maynard, Nick; Park, Min Hae; Wahedally, Muhammed; Trudgill, Nigel; Crosby, Tom; Cromwell, David; Underwood, Tim
Abstract: Background: Perioperative chemotherapy is widely used in the treatment of oesophageal cancer with substantial survival benefit over surgery alone. However, the postoperative part of these regimens is given in less than half of cases, reflecting uncertainty about its benefit. This study estimates the effect of postoperative chemotherapy after surgery for oesophageal cancer using a large population-based dataset and modern statistical methods. Methods: Patients with oesophageal adenocarcinoma diagnosed between 2012 and 2018 and underwent preoperative chemotherapy followed by surgery, were identified from a national level audit in England and Wales (National Oesophagogastric Cancer Audit). Postoperative therapy was defined as the receipt of at least one cycle of systemic chemotherapy within 90 days of surgery. The comparative effectiveness of postoperative chemotherapy compared to observation was estimated using inverse propensity treatment weighting (IPTW). Results: The study included 2, 814 patients, in whom postoperative therapy was given to 1, 054 (37.5%). Patients who received postoperative therapy were younger, with a lower ASA grade and were less likely to have surgical complications of any type, including anastomotic leak (all p < 0.001). Tumour characteristics were similar in both groups. Weighted median survival times for patients having no treatment or postoperative chemotherapy were 45.4 months and 57.5 months respectively. There was a life expectancy difference at five years of 2.9 months in favour of postoperative chemotherapy (95%CI 1.1–4.8 months, p < 0.001) with a Hazard Ratio of 0.80 (95%CI 0.70-0.91, p < 0.001). Conclusions: Among patients with oesophageal adenocarcinoma treated with preoperative chemotherapy and surgery, improved overall survival was observed in those patients who received postoperative chemotherapy. Minimising surgical complications and improving patient fitness could increase the use of postoperative chemotherapy, leading to better outcomes for patients with oesophageal adenocarcinoma.